Leiomyosarcoma of the small bowel: Report of a case and review of the literature. (2015) - Luis, Joshua; Ejtehadi, Farshid; Howlett, David C.; Donnellan, Imelda M.
Highlights: Case of 83 year old gentleman with chronic anaemia and ominous GI symptoms but unremarkable initial examination and investigations. Leiomyosarcomas of the small bowel is extremely rare and can be differentiated from gastrointestinal stromal tumours by immunohistochemical methods. Imaging in the form of MRE, CT colonography or WCE are crucial when faced with a differential diagnosis of small bowel malignancy. Abstract: INTRODUCTION: Leiomyosarcoma of the small bowel is an extremely rare form of gastrointestinal malignancy. Small bowel tumours are usually asymptomatic at the early stages, and difficult to visualise by upper and lower endoscopy. PRESENTATION OF CASE: An 83-year-old gentleman presented in surgical outpatient clinic with chronic anaemia, abdominal discomfort and a single episode of malaena. Initial OGD and colonoscopy were both unremarkable. Subsequent CT revealed a mass in the right iliac fossa of likely small bowel origin, leading to an urgent laparotomy and resection with primary anastomosis. Histopathology showed a high grade leiomyosarcoma with no signs of metastasis and confirmatory immunological staining. Post-surgery follow up remains unremarkable. DISCUSSION: Leiomyosarcomas of the small bowel are extremely rare entities, particularly following the advent of robust immunohistological diagnostic methods allowing differentiation from GISTs. As small bowel tumours are often not visualised by upper and lower endoscopy, further investigations to visualise the small bowel are crucial, generally in the form of magnetic resonance enterography, CT colonography or wireless capsule endoscopy. CONCLUSION: The treatment of such tumours remains predominantly centred around surgical resection, and prognosis is dependent on tumour size and histological staging.